Exploring Student Perceptions of Technological Pedagogical Content Knowledge (TPACK) in Translation Courses - Rosalina, Utami; Sahronih, Siti; Sopian, Topik (Jurnal Pendidikan dan Pengajaran, 2024)
Technological Pedagogical Content Knowledge (TPACK) is regarded as one of the most significant models for showcasing students' perceptions in translation courses. This study was undertaken to investigate the perceptions of both novice and experienced translation students from institute Pendidikan dan Bahasa Invada regarding the utilization of technological pedagogical content knowledge in professional development teaching. In pursuit of the study's three objectives, the mixmethod method was utilized by the two authors due to its appropriateness. Data gathering involved distributing a 20-item questionnaire to a purposive sample comprising 75 novice and experienced and female translation students chosen from institute Pendidikan dan Bahasa Invada during 2021/2022. Additionally, a significant proportion of the instructors demonstrated an average level of knowledge regarding TPACK. Their perceptions towards TPACK were notably positive. Moreover, the study's results highlighted the substantial role of educational backgrounds in digital technologies in the professional development of novice and experienced translation instructors at IPB Cirebon. The study's implications were deliberated upon, with recommendations proposed to equip all institution in cirebon with educational software, e-learning platforms, teaching software, and to provide novice and experienced translation students’ with sessions on new digital skills, cybersecurity workshops, and innovative digital skills training.